(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
In this paper, we will analyse Political Islam based on three cases in very different geographical locations, at varying stages of development and which have sought different solutions to problems and challenges. All with the aim of demonstrating, as the title suggests, the plurality or, if you like, the complexity or diversity of a political movement that is far from monolithic.